THE CHEMICAL CHARACTERISTICS OF RICE ANALOGS OF CASSAVA WITH THE ADDITION OF A MIXTURE OF PURPLE SWEET POTATO FLOUR AND SAGO FLOUR - Pidata Gina Putri; Novelina Novelina; Alfi Asben (Politeknik Negeri Lampung, 2022)
This study aims to study the effect of adding a mixture of sago flour and purple sweet potato flour on various levels of physical and chemical characteristics of the resulting analogue rice. The results showed that the addition of purple sweet potato flour and sago flour had a significant effect on the analysis of fat content, protein content, antioxidant activity, and amylose content while it had no significant effect on water content, ash content. The best product based on the organoleptic test of analog rice was analog rice product in treatment A (45% addition of sweet potato flour and 5% sago flour). The results of the analysis of treatment A (addition of 45% purple sweet potato flour and 5% sago flour) are 6.51% water content, 1.17% ash content, 1.11% fat content, 3.55% protein content, antioxidant activity 23 ,43%, amylose content 30.92%, gelatinization temperature of 70.4 ° C.